Macrophage migration inhibitory factor (MIF) and the tumor ecosystem: a tale of inflammation, immune escape, and tumor growth - Youness, Rana A.; Elemam, Noha M.; Abdelhamid, Abdelhamid M.; Mohamed, Adham H.; Elsherbiny, Lolowa M.; Ramzy, Asmaa; Assal, Reem A. (Frontiers in Immunology, 2025)
Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine with a pivotal role in immune regulation, inflammation, and tumorigenesis. Originally identified as a T cell-derived factor inhibiting macrophage migration, MIF has since been recognized as a key player in the progression of a wide range of solid tumors. This comprehensive review traces the historical discovery and evolving understanding of MIF, highlighting its structural features, receptor interactions, and intracellular signaling mechanisms. The review also explores the molecular mechanisms of MIF involvement in tumor pathogenesis through promoting proliferation, angiogenesis, immune evasion, and metastasis. Special focus is given to MIF interplay with several oncogenic pathways, modulation of the tumor microenvironment, and its dual role in both autocrine and paracrine signaling within tumors. The review also discusses emerging insights into MIF’s involvement in therapeutic resistance and its potential as a diagnostic biomarker and therapeutic target. By consolidating current knowledge, the authors aim to provide a detailed perspective on MIF’s multifaceted role in solid tumors and to outline future directions for research and clinical intervention.